Os processos de inclus??o social, educa????o e sa??de: uma an??lise qualitativa dos surdos idosos do Distrito Federal - Sousa, Alyne Dayane Pac??fico (2016)
The rapid growth of the elderly population presents important factors that can be analyzed, including as regards the elderly deaf, which unfortunately, are often not covered by shares in social fields, educational and health. This research arises for monitoring this growing number of deaf people who are now in this phase of life and undergo various difficulties in access to these institutions of law. After a consultation with the deaf community opted for data collection in the Instituto Nossa Senhora do Brasil - Inoseb which is a philanthropic organization that for more than 47 years develops a evangelization and inclusion to work with the deaf community in the Distrito Federal. The research consisted of a qualitative and descriptive study through a semi-structured interview, filmed in Libras, and transcribed into Portuguese. For content analysis was used MAXQDA software based on Bardin Content Analysis system. The results showed that the company mostly does not know Pounds and who is not prepared for this type of communication; in relation to education all respondents had the methodology the oralist method, neglecting their peculiarities; and access to health, most always need to be accompanied by a listener relative to assist in communicating with health professionals. It is hoped that this research will allow a singular look at the problems experienced by the elderly deaf and serve as support for institutions aimed at serving this portion of society.